Globea orixensis Roxb. (Zingiberaceae) - A New Record for the Flora of Assam, India - Darlong, Lalawmkima; Bhattacharyya, Debjyoti (Journal of the Bombay Natural History Society (JBNHS), 2011)
No Abstract.